Studi Peran Pendidikan Vokasional dalam Adopsi Teknologi Pertanian Modern di Daerah Terpencil - Ayu Dian Pratiwi Permatahati; Suci Amalia; Sa’idy; Ahmad Mashudi (CV. Creative Tugu Pena, 2022)
The This study aims to examine the role of vocational education in promoting the adoption of modern agricultural technologies in remote areas, with a specific focus on the Lampung region. The rapid development of agricultural technologies requires farmers to possess strong technical competencies in order to enhance both productivity and the sustainability of farming practices. Vocational education serves as an alternative educational model that emphasizes practical and applicable skills, making it highly relevant to the real-world needs of farmers. This research employs a descriptive qualitative approach, utilizing data collection methods such as surveys, in-depth interviews, and direct observations. The findings are expected to inform the development of vocational education policies that are responsive to local needs. Moreover, the study aims to formulate strategies to optimize the role of vocational education in supporting the digital transformation of agriculture. This research is crucial for strengthening food security and promoting sustainable rural development in the era of modernization. This study contributes to the academic and policy discourse by highlighting the pivotal role of vocational education in bridging the gap between technological advancement and practical implementation in rural farming communities. It offers a contextualized framework for integrating vocational training into agricultural development strategies and provides actionable insights for policymakers, educators, and development practitioners working to modernize agriculture in remote areas.